1998
DOI: 10.1021/cm970603i
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Sulfate and Chloride Anions on a Well-Characterized Al 2024 Electrode

Abstract: We studied sorption processes, adsorption and incorporation, of sulfate and chloride anions on the surface of well-characterized aluminum 2024 alloy using electrochemical, radiochemical, and ultrahigh-vacuum spectroscopic techniques. The measurements were carried out at an open-circuit potential and in the electrode potential range on the negative side of the open-circuit potential (cathodic polarization conditions), at various pH values. The focus was on sorption reversibility as well as on the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The interest in CO adsorption is mainly due to the detrimental role of adsorbed carbon monoxide in electrocatalysis, where it often acts as a poisoning intermediate that blocks active surface sites. This blocking effect, however, can be positive in other cases, for example in corrosion, a field that has also attracted Wieckowski's attention [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in CO adsorption is mainly due to the detrimental role of adsorbed carbon monoxide in electrocatalysis, where it often acts as a poisoning intermediate that blocks active surface sites. This blocking effect, however, can be positive in other cases, for example in corrosion, a field that has also attracted Wieckowski's attention [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This does not seem to be the case in the OY water environment. Studies were carried out on pure aluminum and 2024 alloy showing the influence of sulfates and chlorides in sulfate, perchlorate or phosphate supported solutions 7, 13–16. It was revealed that SO 4 2− ions delay pit initiation by competitive adsorption with Cl − ions but accelerate the growth of pre‐existing pits.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54] Computationally, fluorination of AlOH groups using HF gas has been predicted to be energetically favorable. [62][63][64] In this work, we report DFT energetics associated with Cl − →OH − on the α-Al 2 O 3 (0001) surface using parameters consistent with those we apply to examine Cl − insertion into V O inside the oxide film, so that a comparison of mechanisms can be made. The passivating alumina films on Al metal surfaces are known to be amorphous.…”
Section: Introductionmentioning
confidence: 99%